Electrical Engineering Students’ Perception in a Flipped Classroom Pedagogy - Mupita, Jonah; Abdulah, Ade Gafar; Hakim, Dadang Lukman; Saripudin, Saripudin; Subekti, Eri (INVOTEC, 2021)
Tertiary learning institutions are under immense pressure to evolve within the realms of the fourth industrial revolution. The flipped classroom model externalizes in-class traditional learning and internalizes outside class activities in an attempt to move students from lower order cognitive skills to higher order cognitive skills. Training institutions are anticipated to minimize learning costs in the face of increasing enrollments. The broad aim of the study was to establish whether a flipped pedagogy would enhance performance and improve students’ perceptions over the conventional classroom pedagogy. To examine the impact of a flipped learning model, an experiment was conducted on two classes studying fundamentals of electrical engineering course. The participants were 64 pure electrical engineering students sampled from a population of 156 first year electrical engineering students. 32 students were assigned to the experimental group which was exposed to both the flipped classroom model and traditional classroom model. The remaining 32 were solely exposed to the traditional classroom pedagogy. Evaluation survey was administered on both the flipped and traditional cohort. Although students revealed positive perceptions of the flipped classroom model, empirically, there was no significant differences in academic achievements of students taught using either instructional approach. 83.87% of the flipped students were better off with a conflated instructional pedagogy as canvassed through the questionnaire survey. Educational practitioners ought to move up with the fourth industrial revolution demands by adopting a blended instructional approach.